(untitled) (Economic and Political Thought, 2012)
Terrorism means using violence and evoking the feeling of threat, fear and hatred by various political, international, social and religious organizations. It is a specific form of political fight. It has accompanied people since the dawn of time and evokes the feeling of permanent threat among states and nations all over the world. The article aims at showing terrorism as a threat for the contemporary international relations and the development of a new international order. The author tries to present the specificity of contemporary terrorism and its sources, and answer the question what makes terrorism different from the fight for national independence. He shows that contemporary terrorism is a synthesis of everything that is worst in the life of every man, i.e. fear, aggression, manipulation, forcing people and institutions to act against their will and violating basic human rights. It is a weapon in the hands of the weak that want to strike harmfully and in a spectacular way because they cannot create a real threat on a bigger scale. The main thesis of the article is a statement that international terrorism, which has been getting stronger since the beginning of the 21st century, is one of the biggest threats for the contemporary world. The article was based on the abundant topical literature, published documents, and press and Internet sources. Its aim is to make the readers, especially politicians, aware of the fact that terrorist threat exists all the time; it has not gone and it is only a question of time when terrorists will let us know about them again striking harmfully where nobody will expect that.